2014
DOI: 10.1128/aem.04168-13
|View full text |Cite
|
Sign up to set email alerts
|

New Skin Test for Detection of Bovine Tuberculosis on the Basis of Antigen-Displaying Polyester Inclusions Produced by Recombinant Escherichia coli

Abstract: cThe tuberculin skin test for diagnosing tuberculosis (TB) in cattle lacks specificity if animals are sensitized to environmental mycobacteria, as some antigens in purified protein derivative (PPD) prepared from Mycobacterium bovis are present in nonpathogenic mycobacteria. Three immunodominant TB antigens, ESAT6, CFP10, and Rv3615c, are present in members of the pathogenic Mycobacterium tuberculosis complex but absent from the majority of environmental mycobacteria. These TB antigens have the potential to enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 43 publications
1
33
0
Order By: Relevance
“…Interestingly, immunological studies using antigen-displaying beads revealed that the beads showed adjuvant properties by enhancing the immune response to the displayed antigen, compared to its soluble counterpart (18). This paper extends findings from the earlier study (11) by demonstrating that biobeads displaying ESAT-6, CFP10, and Rv3615c (3-protein biobeads) were effective in identifying experimentally and naturally M. bovis-infected cattle, as well as distinguishing them from BCG-vaccinated noninfected animals. In addition, biobeads were designed and produced to display four mycobacterial proteins, i.e., ESAT-6, CFP10, Rv3615c, and Rv3020c (4-protein biobeads) simultaneously, potentially increasing test sensitivity (10).…”
supporting
confidence: 74%
See 3 more Smart Citations
“…Interestingly, immunological studies using antigen-displaying beads revealed that the beads showed adjuvant properties by enhancing the immune response to the displayed antigen, compared to its soluble counterpart (18). This paper extends findings from the earlier study (11) by demonstrating that biobeads displaying ESAT-6, CFP10, and Rv3615c (3-protein biobeads) were effective in identifying experimentally and naturally M. bovis-infected cattle, as well as distinguishing them from BCG-vaccinated noninfected animals. In addition, biobeads were designed and produced to display four mycobacterial proteins, i.e., ESAT-6, CFP10, Rv3615c, and Rv3020c (4-protein biobeads) simultaneously, potentially increasing test sensitivity (10).…”
supporting
confidence: 74%
“…As the skin test is the primary screening test for TB diagnosis in cattle, the cost of the skin test reagents is an important consideration. It was reported recently that display of three specific mycobacterial proteins (ESAT-6, CFP10, and Rv3615c) on bacteria-produced polyester inclusions (biobeads) could greatly increase their immunogenicity for the skin test (11). This markedly reduces the cost of the reagents, as lower concentrations of the proteins can be used and only a single fermentation is required with the proteins displayed as a fusion protein on single biobeads.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A potential problem with the use of these antigens in a primary screening skin test would be the cost of the reagents. A recent study has shown that these antigens could be displayed on polyester inclusion bodies produced in bacteria such as Escherichia coli (Biobeads), producing a skin test reagent with a high sensitivity and specificity [84]. The cost of production of these Biobeads displaying a fusion protein of these three proteins is markedly lower than that of recombinant proteins or peptides as the antigens are used at very low concentrations due to their high immunogenicity and they are produced by fermentation technology.…”
Section: Diva Testsmentioning
confidence: 99%